Perancangan User Interface Aplikasi “Impruv” Sebagai Akses Digital Layanan Kesehatan Mental - Septianingrum, Zachrani; Nadia, Zita (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2022)
In Indonesia, the prevalence rate of mental emotional disorders is quite high. The Indonesian Ministry of Health stated that the number of people with mental disorders had increased by 6.5% during the 2020-2021 period. However, there are still many individuals who do not seek help for their mental health. Some of them do not know how to get access to adequate services. In addition, the rapid development of digital technology can be an important means of providing mental health services that are in line with the needs of the younger generation. The method used in this study is qualitative method. The purpose of this study is to design a mental health consultation application user interface that is in accordance with user needs so as to improve mental health services to be more effective and efficient. It is hoped that this application design can make it easier for the public to get access to mental health services.